Shaping the future: recent advances of 3D printing in drug delivery and healthcare. (3rd October 2019) - Trenfield, Sarah J; Awad, Atheer; Madla, Christine M; Hatton, Grace B; Firth, Jack; Goyanes, Alvaro; Gaisford, Simon; Basit, Abdul W
ABSTRACT: Introduction : Three-dimensional (3D) printing is a relatively new, rapid manufacturing technology that has found promising applications in the drug delivery and medical sectors. Arguably, never before has the healthcare industry experienced such a transformative technology. This review aims to discuss the state of the art of 3D printing technology in healthcare and drug delivery. Areas covered : The current and future applications of printing technologies within drug delivery and medicine have been discussed. The latest innovations in 3D printing of customized medical devices, drug-eluting implants, and printlets (3D-printed tablets) with a tailored dose, shape, size, and release characteristics have been covered. The review also covers the state of the art of 3D printing in healthcare (covering topics such as dentistry, surgical and bioprinting of patient-specific organs), as well as the potential of recent innovations, such as 4D printing, to shape the future of drug delivery and to improve treatment pathways for patients. Expert opinion : A future perspective is provided on the potential for 3D printing in healthcare, covering strategies to overcome the major barriers to integration that are faced today.